Connecting our community 5.0 and AMSA health day: the first student-led face-to-face community engagement after COVID-19 - Ismail, Ilham Ameera; Mazlan, Mohamad Aiman (Faculty of Medicine, 2022)
The medical students and the medical fraternity have always been very close to the community. Sekretariat Mahasiswa Fakulti , Fakulti Perubatan (SMF) has been consistently and actively involved in community engagements in the past years. Unfortunately, the COVID-19 pandemic has caused a halt to student-led face-to-face (FTF) community engagements. In 2020 and 2021, most community engagements are cancel ed or held entirely online. Although an online program may have the potential of having more participants as they are not limited to a specific geographical location, the participation would depend on the ability of the participants to join the online program.